2022
DOI: 10.1186/s43066-022-00188-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sustained virologic response in regression of portal hypertension in Egyptian patients with hepatitis C virus-associated cirrhosis and portal hypertension

Abstract: Background Portal hypertension (PH) is a common consequence in hepatitis C virus cirrhotic patients. With interferon alpha-based therapy, SVR was linked to improved PH and fibrosis regression. SVR to oral antiviral regimens is linked to reduced portal pressure in patients with clinically significant portal hypertension (CSPH) at baseline. However, CSPH continues in most of the patients. This study aims to assess the reversibility and/or improvement of PH in Egyptian patients with HCV-related ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(36 reference statements)
3
2
0
1
Order By: Relevance
“…In the current study, total bilirubin was found to be higher in patients with varices than in patients without varices with statistical significance. This came in agreement with [32] who documented that a high total bilirubin level was found with varices presence. On the other hand, [33] showed no association between bilirubin level with esophageal varices.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, total bilirubin was found to be higher in patients with varices than in patients without varices with statistical significance. This came in agreement with [32] who documented that a high total bilirubin level was found with varices presence. On the other hand, [33] showed no association between bilirubin level with esophageal varices.…”
Section: Resultssupporting
confidence: 92%
“…As shown in Table 2 the findings of the studied groups revealed that there was significantly higher (P-< 0.000) mean values of spleen diameter, portal vein diameter, and ascites between both groups A and B. This came in agreement with the study of Faheem et al [32] who found that portal vein diameter and spleen diameter which are indirect predictors of portal hemodynamics can be used effectively as a screening test without subjecting patients to EGD.…”
Section: Resultssupporting
confidence: 88%
“…HCC developed in 2 patients at 12 weeks after EOT (SVR) and 4 patients at 24 weeks after SVR without any significance which was consistent with a large Egyptian study conducted by Shiha et al who found that HCC incidence decreased in HCV-related decompensated patients who achieved SVR [25]. The number of ascetic patients was significantly decreased at 24 weeks after SVR compared to baseline which might be attributed to DAAs' ability to reduce further hepatic decompensation and portal hypertension that reported by many studies [20,22]…”
Section: Discussionsupporting
confidence: 84%
“…31 Some studies have shown that most patients who achieve the SVR by DAA treatment experienced a significant decrease in the portal pressure 32,33 and an increase in the portal blood flow velocity. 34,35 Since slow portal blood flow is a major risk factor for the development of PVT, 2 this might partly explain the low incidence of PVT in our cohort.…”
Section: Discussionmentioning
confidence: 88%